The Hard Lessons Learned by the COVID-19 Epidemic in Italy: Rethinking the Role of the National Health Care Service? - Philippe Primo Caimmi; Andrea Capponi; Fabrizio Leigheb; Franca Dall' Occo; Roberto Sacco; Mario Minola; Emmanouil Ioannis Kapetanakis (Springer, 2021)
The dramatic events precipitated by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus pandemic have highlighted the limitations and contradictions of our country's current health care delivery model plagued by the closure of healthcare delivery structures, staff reductions, privatizations and inadequate funding which have been affecting the Italian National Health System during the past 10 years. The COVID-19 epidemic has a hefty bill: thousands of deaths - mainly elderly, hospitals overwhelmed, residential assistance structures reaching their limits, sick people left alone and uncared in homes, the disruption in life habits and an altered daily way of living never experienced before; all have contributed into making the ongoing tragedy even more painful. Herewith, we present and discuss the information and reflections from our experiences and postulate the rethinking of the established socio-health policies not only in Italy but also in other western countries which have failed to curtail the epidemic via conventional management approaches.